Development of a Fluorescence Immunoassay Based on Curcumin Carbon Dots-labeled IgY Antibodies for SARS-CoV-2 Detection - Rachmadani, Nisa Amanda; Soetomo, Meilisa Keizia; Taharuddin, Audrey Angelina Putri; Santika, Arum Sinda; Abdillah, Oktaviardi Bityasmawan; Permatasari, Fitri Aulia; Iskandar, Ferry; Rachmawati, Heni; Fibriani, Azzania (Bogor Agricultural University, Indonesia, 2026)
Carbon dots (CDs) are widely utilized in biomedical applications as fluorescent labels for imaging and diagnostics due to their excellent biocompatibility and superior optical properties. These advantages often make CDs a substitute for organic fluorescent dyes, which suffer from low emission intensity and poor photostability when interacting with biomolecules. Moreover, carbon-based materials are eco-friendly and can be synthesized from natural sources, such as curcumin, a chromophore compound abundantly available in Indonesia. Therefore, this study conducted a preliminary investigation on curcumin CDs-labeled IgY antibodies (IgY-cur CDs) for fluorescence immunoassay of SARS-CoV-2 in rapid test applications. The synthesis of the fluorescent label involved a carbodiimide coupling reaction using EDC/NHS agents to conjugate IgY antibodies with curcumin CDs. The IgY-cur CDs conjugate was confirmed to detect antigens through FRET immunosensor mechanisms, showing a significant increase in fluorescence intensity with increasing antigen concentrations (p < 0.05), with a minimum sample concentration of 10 ng. Furthermore, the IgY-CDs cur conjugate was applied as a reporter in a fluorescence-based LFIA using a sandwich assay format. The test strip successfully detected synthetic multiepitope SARS-CoV-2 antigens with an estimated detection limit of 54.28 µg and nasopharyngeal samples from confirmed COVID-19 patients within 35 minutes of operation. The test strip was evaluated to be stable under cold storage at 4°C for up to 3 weeks. In conclusion, curcumin CDs-labeled IgY antibodies demonstrate promising potential for further development as fluorescent labels in rapid diagnostic applications targeting SARS-CoV-2.